2018
DOI: 10.3390/w10040450
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Regularized Dynamic System Response Curve for Real-Time Flood Forecasting Correction

Abstract: Abstract:The dynamic system response curve (DSRC) is commonly applied as a real-time flood forecasting error correction method to improve the accuracy of real-time flood forecasting. It has been widely recognized that the least squares (OLS/LS) method, employed by DSRC, breaks down ill-posed problems, and therefore, the DSRC method may lead to deterioration in performance caused by meaningless solutions. To address this problem, a diagnostically theoretical analysis was conducted to investigate the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…As illustrated in Figure 2h, XAJ tends to underestimate total water volume in general. Sun et al [65] reported similar results and concluded that underestimates of free water storage lead to underestimates of total water volume. In addition, WetSpa systematically overestimates total runoff volume.…”
Section: Comparing Different Model Structuresmentioning
confidence: 71%
“…As illustrated in Figure 2h, XAJ tends to underestimate total water volume in general. Sun et al [65] reported similar results and concluded that underestimates of free water storage lead to underestimates of total water volume. In addition, WetSpa systematically overestimates total runoff volume.…”
Section: Comparing Different Model Structuresmentioning
confidence: 71%
“…It is worth noting that uncertainty may stem from several sources, such as model structure, model parameters, model states, and initial conditions (Clark & Vrugt, 2006; Kuczera et al, 2006; Sun, Bao, Jiang, Ji, et al, 2018). However, in this study, we only update the model state, indicating all the uncertainties are attributed to state uncertainty, which may result in model states being twisted but a satisfactory performance from the perspective of the model residual (Sun, Bao, Jiang, Si, et al, 2018). Therefore, future work is needed to take other uncertainties into account, such as extending the state estimation to the joint state parameter estimation, which considers the uncertainties of model state and model parameters simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the first-order Taylor linearization to approximate the hydrologic model, error correction is achieved by solving the corresponding equations using the least square method. The DSRC method was initially applied to correct single hydrological elements, including runoff [15], rainfall [16] and model state variables [17]. Then, it was used to correct several hydrological elements comprehensively [18].…”
Section: Introductionmentioning
confidence: 99%
“…Then, it was used to correct several hydrological elements comprehensively [18]. However, some studies [17][18][19][20] found that the correction results are not always stable, reflected in the excessive correction of hydrological element series and none-smooth simulated flow hydrographs. To solve the above problems, the DSRC-R method was developed by Si et al [19] from the point of the regularization known as ridge estimation, and this method has improved the stability of correction results to some degree.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation